Fibroblast Growth Factor 22 Contributes to the Development of Retinal Nerve Terminals in the Dorsal Lateral Geniculate Nucleus - Singh, Rishabh; Su, Jianmin; Brooks, Justin M.; Terauchi, Akiko; Umemori, Hisashi; Fox, Michael A. (Frontiers in Molecular Neuroscience, 2012)
At least three forms of signaling between pre and postsynaptic partners are necessary during synapse formation. First, ‘targeting’ signals instruct presynaptic axons to recognize and adhere to the correct portion of a postsynaptic target cell. Second, trans-synaptic ‘organizing’ signals induce differentiation in their synaptic partner so that each side of the synapse is specialized for synaptic transmission. Finally, in many regions of the nervous system an excess of synapses are initially formed, therefore ‘refinement’ signals must either stabilize or destabilize the synapse to reinforce or eliminate connections, respectively. Because of both their importance in processing visual information and their accessibility, retinogeniculate synapses have served as a model for studying synaptic development. Molecular signals that drive retinogeniculate ‘targeting’ and ‘refinement’ have been identified, however, little is known about what ‘organizing’ cues are necessary for the differentiation of retinal axons into presynaptic terminals. Here we show that fibroblast growth factor 22 (FGF22) is required for the timely organization of retinogeniculate synapses. To identify ‘organizing’ cues, we used microarray analysis to assess whether any target-derived ‘synaptic organizers’ were enriched in the mouse dorsal lateral geniculate nucleus (dLGN) during retinogeniculate synapse formation. One candidate ‘organizing’ molecule enriched in perinatal dLGN was FGF22, a secreted cue that induces the formation of excitatory nerve terminals in muscle, hippocampus and cerebellum. In FGF22 knockout mice, the development of retinal terminals in dLGN was impaired. Thus, FGF22 is an important ‘organizing’ cue for retinogeniculate synapses.